2012
DOI: 10.1128/jvi.07150-11
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Porcine Epidemic Diarrhea Virus Variant

Abstract: In 2011, outbreaks of viral diarrhea were observed on most swine-breeding farms in most of the provinces of China. The disease is characterized by vomiting, severe diarrhea, and a high mortality rate (82.3%) in newborn piglets. The clinical appearance was similar to that of porcine epidemic diarrhea virus (PEDV) infection. PEDVs were detected in samples (feces or small intestines) from most farms. In order to investigate whether there is a PEDV variant circulating in China, we sequenced and analyzed the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 5 publications
8
50
0
Order By: Relevance
“…Most of the diversity between the recent field strains in G1-1 and in G2 is located within the 1100 nt-domain. The phenomenon is also found in the S gene of CH/FJND-3/2011 [17]. …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most of the diversity between the recent field strains in G1-1 and in G2 is located within the 1100 nt-domain. The phenomenon is also found in the S gene of CH/FJND-3/2011 [17]. …”
Section: Discussionmentioning
confidence: 88%
“…Our previously study indicated that the S gene of CH/FJND-3/2011) has the lowest sequence homology (93.75%) with that of CH/S and is 9 nt longer than those of CV777 and CH/S [17]. A more precise study with the full-length S genes of recently Chinese field strains will help to best understand the genetic relationships among prevailing PEDV in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, since December 2010, large‐scale outbreaks of diarrhea with 80–100% morbidity and 50–90% mortality in suckling piglets have occurred in most Chinese provinces, affecting even vaccinated pigs . Investigations indicated that these large‐scale outbreaks of diarrhea were caused by a variant of PEDV . New PEDV outbreaks have also occurred in Vietnam, Thailand, Korea, and the United States, where PEDV was considered an exotic before 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus (PEDV), a member of the alphacoronaviruses (family Coronaviridae, order Nidovirales), is a singlestranded, positive-sense RNA virus that causes disease in swine with great financial losses (Chen et al, 2012). The PEDV genome comprises two overlapping open reading frames (ORFs) encoding two polyproteins (pp1a and pp1ab) and five other proteins, spike (S), ORF3, envelope (E), membrane (M), and nucleocapsid (N).…”
Section: Introductionmentioning
confidence: 99%